ANALISIS PENGARUH PERGANTIAN KANTOR AKUNTAN PUBLIK DAN OPINI AUDIT TERHADAP REAKSI PASAR - Ngaijan ngaijan (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2017)
The enactment of the Finance Minister regarding policy changes KAP rotation over a certain period , makes the phenomenon interesting turn of auditors or accounting firm to be assessed . This is because many factors can affect the turnover auditor or accounting firm that carried out by the company and it can be influenced by external factors and internal factors . Auditor turnover can also be a trigger for the market reaction.The study population is a company registered in LQ 45 in 2008-2010 . The sample using purposive sampling method, in which the sample is selected based on criteria teitentu . The criteria used in selecting the sample of this study are as follows : ( 1 ) Company registered in LQ 45 during the years 2008-2010. ( 2 ) the Company's audited keuanganya reports from 2008-2010 that included the name of the firm or its auditors and statements contained Opinion of KAP about the fairness of financial statements . ( 3 ) The company has a complete stock of data available on the IDX database during 2008-2010 . Data analysis was performed using multiple linear regression.Results of hypothesis testing concluded that : ( 1 ) Substitution of auditors ( from Big 4 to non- Big 4 and otherwise ) affects the market reaction . Substitution of the big 4 to non- Big 4 responded negatively by the market and instead turn of non big 4 big 4 responded to positively by the market . ( 2 ) audit opinion affect the market reaction , firms with audit opinion other than " unqualified " tends to get a negative reaction compared with the companies that opinion " unqualified . ( 3 ) As much as 51.3 % of the variation is explained by the change in abnormal return audit opinion , the auditor change , auditor tenure and the size of the company, while 48.7 % described other variables in addition to the audit opinion , the auditor change , auditor tenure and size of company.Keywords : Change of auditor, Big four, Non big four, The market reactionDitetapkannya kebijakan Menteri Keuangan mengenai rotasi pergantian KAP selama jangka waktu tertentu, menjadikan fenomena pergantian auditor atau KAP menarik untuk dikaji. Hal ini dikarenakan banyak faktor yang dapat mempengaruhi pergantian auditor atau KAP yang dilakukan oleh perusahaan dan hal tersebut dapat dipengaruhi oleh faktor-faktor eksternal maupun faktor internal perusahaan. Pergantian auditor juga dapat menjadi pemicu reaksi pasar.Populasi penelitian ini adalah perusahaan yang terdaftar di LQ 45 pada tahun 2008-2010 sebanyak 45 perusahaan selama 3 tahun periode penelitian, sehingga total didapatkan 135 sampel. Analisis data dilakukan dengan menggunakan regresi linier berganda.Hasil dari pengujian hipotesis disimpulkan bahwa: (1) Pergantian auditor (dari big 4 ke non big 4 dan sebaliknya) berpengaruh terhadap reaksi pasar. Pergantian dari big 4 ke non big 4 direspond negatif oleh pasar dan sebaliknya pergantian dari non big 4 ke big 4 direspond positif oleh pasar. (2) Opini audit berpengaruh terhadap reaksi pasar, perusahaan-perusahaan dengan opini audit selain ―wajar tanpa pengecualian‖ cenderung mendapatkan reaksi negatif dibandingkan dengan perusahaan yang mendapatkan opini ―wajar tanpa pengecualian. (3) Sebesar 51,3% variasi perubahan abnormal return dijelaskan oleh opini audit, pergantian auditor, auditor tenure dan ukuran perusahaan sedangkan 48,7% dijelaskan variabel lain selain opini audit, pergantian auditor, auditor tenure dan ukuran perusahaan.Kata kunci : Pergantian auditor, Big four, Non big four, Reaksi pasar